The role of servicescape as a driver of customer value in experience-centric service organizations: the Dragon Football Stadium case - Teresa Fernandes (2014)
Service experience is the core of service offering. However, research on the role of the service environment when creating experiences is still underdeveloped, and even less empirical evidence is available that relates servicescape with customers' perceptions of value. Our purpose is to focus on the role of servicescape as a driver of customer experience by analyzing its impact on customer value creation and behavior. We have chosen an experience-centric service organization, a football club, to develop our analysis. A regression analysis was performed to determine the main drivers of value among â sportscapeâ components and how it influenced customers' attitude and behavior. A total of 349 questionnaires were collected during a match of the Portuguese Football League at Dragon Stadium. Our analysis showed that servicescape influences consumer perceived value, attitudes, and behavior when creating service experiences: value-in-context generates customers' satisfaction, which in turn has a positive effect on their desire to repeat the experience.